Efficacy of Pre and Postoperative Antibiotics in Percutaneous Pinning of Pediatric Supracondylar Humerus Fractures - Farhan Majeed, Mudassir Siddique. Maham Ashraf, Moshin Tahir, Ahmad Shams, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Supracondylar humerus (SCH) fracture is a common injury to the pediatric age group and often requires closed reduction and percutaneous pinning. Much controversy exists in the literature regarding the use of antibiotics in the pre-operative or postoperative period with some centers administrating a single pre-operative dose only, whereas other administering a single pre-operative dose along with few post-operative doses and some centers where no antibiotic is administrated at all. The purpose of this study is to evaluate the incidence of surgical site infection in patients receiving a single pre-operative dose only versus single pre-operative along with five days dosage as per local ward policy. Material and methods: We prospectively studied 50 patients at The Children Hospital and Institute of Child Health, Lahore between February 1st, 2021 and July 30th 2021. Following approval from the Institutional Ethical committee, 50 pediatric patients presenting to the Emergency and outpatient department with trauma to affected elbow with Supracondylar humerus fracture were admitted and divided into two equal groups. Group A was given a single pre-operative antibiotic injectable 30 minutes before procedure whereas Group B was given a single pre-operative injectable and another injectable dose on 0 Post-operative day, then oral BD dose for next 5 days which is the routinely followed protocol in our ward setting. Closed Surgical Fixation following manipulation under anesthesia (MUA) with K-wires was performed in each group and Half Cast above elbow was applied for 4 weeks. Patients were discharged on the first post-operative day and called for follow up 2, 4 and 6 weeks. K-wires were removed at 4th week and Range of motion exercises started. Wounds were evaluated at 6th week for surgical site infection. Erythema around the K-wire or any discharge around the wire was labelled as pin tract or surgical site infection. Chi-Square test was used as a significance test and a p-value of 0.05 was considered as significant. Results: Of the 50 patients, there were 32 (58.20%) males and 18 (32.70%) females with the mean age of 4.84 ± 1.87. There were 27 patients aged between 2-4 years, 16 between ages 5-7 and 7 between 8-10 years. Subjects presenting following Fall while playing and fall from height were equal in number, 23 (41.8%) and Fall due to road traffic accident was a less common than the former two with 4 (7.30%) subjects. Two (8%) patients from group A and 1 (4%) patient from group B developed pin tract infection. There was no statistical difference between the two groups (p-value = 0.552) Practical implication of this study includes the rational use of antibiotics in young patients. This will prevent avoidable overuse of antibiotics which is one of the major factors in the development of resistance against pathogens. It will also decrease the economic burden on the healthcare as well as the patient attendants. Conclusion: Our data suggests no added advantage of post-operative antibiotic in contrast to single pre-operative antibiotic when fixing a supracondylar fracture of humerus. Of the complications listed in literature, Pin tract infection remains a rare complication following Closed pinning of supracondylar humerus fracture in pediatric population. Keyword: Antibiotic Prophylaxis, Close Pinning, K-wire fixation, Pin Tract infection, Supracondylar Fracture Humerus